Florida public hurricane loss model: Software system for insurance loss projection. (1st April 2022) - Tao, Yudong; Wang, Tianyi; Sun, Anchen; Hamid, Shahid S.; Chen, Shu‐Ching; Shyu, Mei‐Ling
Abstract: A six‐month‐long Atlantic hurricane season impacts Florida residents every year and can result in devastating consequences, including loss of life, property damage, and business interruptions. Hurricane risk assessment and loss prediction are critical to various uses such as determining homeowner insurance premiums, regulating these premiums, conducting scenario analysis, conducting stress tests for companies, disaster management, and evaluating the benefits of disaster mitigation techniques. This article describes the Florida Public Hurricane Loss Model (FPHLM): a large‐scale catastrophe model with massive databases and analytics tools for business and government decision‐making. We will discuss the design and implementation of each component in FPHLM and explain the tools and techniques utilized to tackle challenges in data availability, data analytics, and the interface between the data, analytical techniques, and computing. Results are shown to validate the software system's effectiveness and reliability and illustrate some of the system's use cases.